A Case of Vaginal Stillbirth in the Presence of Placenta Previa at 33 Weeks of Gestation - Yukiko Chinen; Tadatsugu Kinjo; Hayase Nitta; Yui Kinjo; Hitoshi Masamoto; Yoichi Aoki (Case Reports in Obstetrics and Gynecology)
It was demonstrated that second- and third-trimester therapeutic termination of pregnancy (TOP) is feasible in cases with placenta previa. We report a 34-year-old woman with complex fetal malformations associated with placenta previa. An ultrasound examination at 21 weeks of gestation revealed fetal growth restriction (FGR) and complex fetal malformations associated with a placenta previa. After extensive information, the parents opted for careful observation. Thereafter, FGR gradually progressed and we observed arrest of end-diastolic velocity of the umbilical artery. Finally, intrauterine fetal death (IUFD) was confirmed at 33 weeks of gestation. Two days after IUFD, the patient experienced labor pain. The placenta and dead fetus weighing 961 g were vaginally delivered, and total bleeding was 270 mL. Although further studies to confirm the dynamic change of the uteroplacental blood flow are necessary to avoid the risk of maternal hemorrhage, vaginal TOP with placenta previa after feticide or IUFD would be feasible.